The effects of mechanical ventilation on heart rate variability and complexity in mice - Kazdağli, H; Ozel, HF; Özbek, MA (Journal of the Hellenic Veterinary Medical Society, 2024)
In a variety of diseases, altered respiratory modulation is often an early sign of autonomic dysfunction. Therefore, understanding and evaluating the effects of artificial ventilation on the autonomic nervous system is vital. The effects of artificial ventilation on autonomic balance have been assessed by heart rate variability using frequency domain and non-linear analysis including fractal complexity and entropy analysis in anesthetized mice. BALB/c mice (n=48) were divided into two groups: Spontaneous breathing and artificial ventilation. The electrocardiograms were recorded. Four different analyses were used: i. frequency domain analysis, ii. Poincaré plots, iii. DFA and iv. Entropy analysis. An unpaired t-test was used for statistical analysis. In a ventilated group, VLF and LF parameters were not changed, whereas the HF parameter was decreased compared to spontaneous breathing mice. DFAα1 was significantly increased due to artificial ventilation but DFAα2 was unchanged. SD2/SD1 ratio was increased, however, SD1 and SD2 were not significantly affected. Also, ApEn and SampEn remained unchanged. HF parameter, DFAα1, and SD2/SD1 were affected by artificial ventilation. Decreased HF and increased DFAα1, further support the notion that HRV is dominated by respiratory sinus arrhythmia at high frequencies, this may be due to decreased vagal tone caused by artificial ventilation.